The Economics of an HIF SPRFD Fusion System in a Desert Region - Helsley, Charles (21st International Symposium on Heavy Ion Inertial Fusion. Autonomous Organization of Education “Nazarbayev University”, 2016)
The economics of the FPC SPRFD fusion power system have been discussed previously by Helsley and Burke (2014) in a general model that was based on marketing of electricity and the production of synthetic fuel from the excess generating capacity...
Keywords: fusion system; desert region; Research Subject Categories::NATURAL SCIENCES::Physics::Elementary particle physics